Peningkatan hasil belajar tematik muatan IPA melalui model Problem Based Learning kelas 5 SDN Pajomblangan, Kedungwuni - Wikriyah Wikriyah (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The low learning outcomes of thematic science content at SDN Pajomblangan are due to the inactivity of students in participating in learning. For this reason, this type of research was conducted using classroom action research (CAR). This study aims to describe the steps in implementing the Problem Based Learning learning model and to find out the improvement in learning outcomes for class 5 science content. Data collection techniques used test techniques and non-test (observation) techniques. The analysis technique uses a quantitative descriptive technique. The results showed that the application of the Problem Based Learning model was able to improve student learning outcomes and activeness. The increase in learning outcomes showed that in the pre-cycle the student's level of completeness was 48%, for the first cycle the completeness level was 71%, and the second cycle the completeness level was 90%. While the increase in student activity in the pre-cycle is 50%, for the first cycle the student activity level is 68%, and the second cycle the student activity level is 87%. Based on the results of the study, it can be concluded that the Problem Based Learning learning model can improve learning outcomes and student activity.